Social Computing and Social Media 6th International Conference, SCSM 2014, Held as Part of HCI International 2014, Heraklion, Crete, Greece, June 22-27, 2014, Proceedings - Meiselwitz, Gabriele (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2014)
This book constitutes the refereed proceedings of the 6th International Conference on Social Computing and Social Media, SCSM 2014, held as part of the 16th International Conference on Human-Computer Interaction, HCII 2014, in Heraklion, Crete, Greece in June 2014, jointly with 13 other thematically conferences. The total of 1476 papers and 220 posters presented at the HCII 2014 conferences were carefully reviewed and selected from 4766 submissions. These papers address the latest research and development efforts and highlight the human aspects of design and use of computing systems. The papers accepted for presentation thoroughly cover the entire field of Human-Computer Interaction, addressing major advances in knowledge and effective use of computers in a variety of application areas. The 56 papers included in this volume are organized in topical sections on designing and evaluating social computing and social media; designing, analyzing and visualizing social networks; online communities and engagement; presence and self in social media; social media, games, gamification and entertainment.